Accessory muscles around the superior radioulnar joint: a morphological study - Paraskevas, George K.; Ioannidis, Orestis (Italian Journal of Anatomy and Embryology, 2011)
During anatomical dissections on 36 human elbow joints, we observed the presence of three muscles around the superior radioulnar joint usually neglected by the classical anatomical literature, the lateral tensor muscle of the annular ligament (with an incidence of 16.6%), the medial tensor muscle of the annular ligament (11.1%) and the accessory supinator muscle (16.6%). We could not establish any association between the subject handedness and the sidedness of these aberrant muscles, neither we found a predominance in sidedness or in gender. Furthermore, we did not notice any significant predominance related to the occupation and specifically to heavy labor occupations. On the contrary we found these muscles to be more common in non-laborers, which supports the assumption that these variants constitute rather genetic than epigenetic traits. The knowledge of such anatomical variants facilitate the surgeon operating in the elbow region to better interpret supernumerary muscular bundles in the operative field.